Kolaborasi Pembuatan Film sebagai Etnografi - Tito Imanda (Antropologi Indonesia, 2018)
This paper explores the conceptual and methodological thinking of an ethnography of a collaborative film making with traditional Javanese performance groups, adapting their work from the stage to the screen. This paper specifically offers ethnography as practical research involving researchers and research subjects conducting film projects together. This project has indeed practical and research objectives. The practical goal is to collaborate with traditional rural performance groups, to help facilitate the exploration of their new media and express themselves through film. The research objective of this project is to record, understand and analyze the process, while laying the foundation for further collaboration and research in other contexts and with different communities.